Desenvolvimento de bebida alcóolica fermentada à base de jambolão e caldo de cana-de-açúcar - Oliveira, Érica Resende e (2015)
The fruit processing for obtaining beverages is a way to add value to raw materials and to better remunerate producers by the increasing in demand. Taking this idea as a premise, this work aiming was to prepare and characterize fermented beverages based on jambolan and sugarcane broth. The raw materials were collected in the city of Goiânia-GO. Five different treatments were developed, by replacing the jambolan pulp by sugarcane broth in different proportions (100% jambolan, 70% jambolan, 50% jambolan, 30% jambolan). The following analysis were performed: acidity, pH, total soluble solids, color instrumental parameters (L, a *, b *, C and H), dry extract, reduced dry extract, ash, sugars, density, protein, sulfates, chlorides, total phenolic compounds, anthocianins, tanins and antioxidant capacity. Sensory analysis was also realized, by applying the acceptance test of structured hedonic scale to 60 tasters. Data were subjected to analysis of variance and Scott-Knot test was used to identify significant differences between the means at 5%. The results of sensory analysis were also analyzed by using the methodology of internal preference map. The alcoholic fermentation presented alcohol content of 8oGL, pH average of 3.5 and soluble solids content average of 5oBrix. Fermented beverages containing higher concentrations of jambolan pulp had the higher content of bioactive compounds. Treatment 1 presented contente of phenolic compounds of 298,76 mg. 100 mL-1, antocianins of 668,49 mg. L-1, tanins of 91,87 mg. 100 mL-1 and 85,24% of antioxidante capacity. Sensory analysis showed that the products were accepted by consumers, presenting overall impression above 6 for all treatments. The treatments showed viable characteristics for the production of alcoholic fermented beverage.